Hubungan Mobilisasi dengan Kelancaran ASI pada ibu Sectio Caesaria di RSUD H.Boejasin Pelaihari Tahun 2024 - Mufdalifah, Nina; Yuliastuti, Erni; Kristiana, Efi; Rusmilawaty, Rusmilawaty (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2025)
Preliminary study conducted from August 24-27, 2024, with 10 post-cesarean section mothers on the second day at the Nifas Room of RSUD H.Boejasin showed that 7 mothers had difficulties in breastfeeding their babies due to pain following the caesarean section. This pain made it challenging for them to find a comfortable position to nurse. The purpose of this study is to determine whether there is a relationship between mobilization and the smoothness of breast milk production in post-cesarean section mothers. This study used an observational analytic design with a cross-sectional approach. The population consisted of all postpartum mothers who had undergone a cesarean section, totaling 30 respondents. The sampling technique used was non-probability sampling with accidental sampling. Data collection instruments were used to gather direct data through observation sheets adapted from a previous study. Data analysis was performed using the Chi-Square test. The Spearman test yielded a p-value of 0.000, which means (p<0.05). This indicates that Ha (alternative hypothesis) is accepted, and Ho (null hypothesis) is rejected, suggesting that there is a significant relationship between mobilization and the smoothness of breast milk production in post-cesarean section mothers at RSUD H. Boejasin Pelaihari. The strength of the relationship is very strong and positive. There is a significant relationship between mobilization and the smoothness of breast milk production in post-cesarean section mothers, with a very strong positive correlation.